2011
DOI: 10.3155/1047-3289.61.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Emission Control Technologies for Auxiliary Engines on Ocean-Going Vessels

Abstract: Large auxiliary engines operated on ocean-going vessels in transit and at berth impact the air quality of populated areas near ports. This paper presents new information on the comparison of emission ranges from three similar engines and the effectiveness of three control technologies: switching to cleaner burning fuels, operating in the low oxides of nitrogen (NO x ) mode, and selective catalytic reduction (SCR). In-use measurements of gaseous (NO x , carbon monoxide [CO], carbon dioxide [CO 2 ]) and fine par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…A system of five equations (1), (2), (5), (6) and 7contains five quantities to be determined , , , , * . In this case, the gas consumption and its heat capacity are known values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A system of five equations (1), (2), (5), (6) and 7contains five quantities to be determined , , , , * . In this case, the gas consumption and its heat capacity are known values.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the main factors affecting the formation of harmful substances in diesel engines has shown that due to the peculiarities of the working process occurring in them, a decrease in emissions of incomplete combustion products, carbon oxides, hydrocarbons and harmful particles is accompanied by an increase in emissions of nitrogen oxides and by contrast [1,2,4,5,6]. Therefore, to ensure that diesel meets current and future standards for harmful emissions, exhaust gas recirculation and a catalytic method for their recovery are widely used to reduce nitrogen oxide emissions [7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the metal oxides formed by oxidation of higher concentration of metals in HFO enhanced the hydrolysis. Jayaram and Nigam [154] conducted an experiment on three auxiliary engines on container vessels and reported that SCR reduced the NOx emission factor to 1.4-2.4g/kWh which corresponded to a reduction of 90-91% for HFO and 82-84% for marine distillate oil respectively. Zhu et al [155] reported that the weighted average of NOx with low-sulfur exhaust gas was 3.08 g/kWh, lower than that of the IMO Tier III regulation while NOx with high-sulfur exhaust gas was 4.17 g/kWh, higher than that of the IMO Tier III regulation.…”
Section: Exhaust Aftertreatment 351 De-noxmentioning
confidence: 99%
“…There are many ocean-going vessels carrying cargo going in and out of the two ports in the Long Beach area, thus making this sector more of a concern for many people. Jayaram et al [ 51 ] illustrated that money can be spent to switch vessels to cleaner-burning fuels and operate in a lower oxide of nitrogen. For refineries, many oil refining companies are operating in the Long Beach area and money can be spent to install air cleaning and monitoring units within the factory and improve factories’ production efficiencies.…”
Section: Decision Context Definition and Decision Alternativesmentioning
confidence: 99%